CORRELATION BETWEEN FAMILY SUPPORT AND BLOOD SUGAR CONTROL COMPLIANCE IN THE PATIENT’S DIABETES MELLITUS TYPE II - Nurwidiyanti, Erika; Afrida, Maryudella; Langkeru, Amikke Lipat (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2023)
Introduction: Diabetes mellitus type II currently appears to be the world's highest disease prevalence with 424,9 million. Compliance with the control of blood sugar regularly is very important to reduce complications in patients with diabetes mellitus. To meet the problems above, there is a need for good family support. The purpose of this study is to know the correlation between family support and compliance with the control of blood sugar in patient's diabetes mellitus type II at Sleman General Hospital, Yogyakarta Province.Methods: This research is quantitative research with a cross-sectional approach. The sample of this study amounted to 55 respondents, taken using a simple random sampling technique. The instrument in this study used family support questionnaires, interviews for regularity of blood sugar control, and crosschecking it in the medical records. The spearman rank correlation test tested the data.Results: Most of the 55 respondents have good family support (50,9%), compliance with control of blood sugar is good (61,8%), and the result of the statistical test obtained a p-value of 0,000 with a coefficient correlation of 0,609.Conclusion: There is a significant correlation between family support and blood sugar control compliance in patient's diabetes mellitus type II. It's expected that the family can support to the patients in compliance with treatment to improve their quality of life.